APPLICATION OF COMMUNICATION ETHICS IN FINANCING PRODUCTS AT ISLAMIC BANKS IN GORONTALO - WIWIN KONI (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2022)
This study aims to find out how to apply communication ethics in financing products at Islamic banks in Gorontalo. this type of research is field research with a qualitative approach. The data sources in this study consisted of primary and secondary data obtained from interviews with Islamic bank managers in Gorontalo, and documentation as well as those sourced from library research in the form of reading books and other sources relevant to this research. This study resulted in the findings that the application of the principles of communication ethics at Islamic banks in Gorontalo is not only a slogan, but is an integral part of the pattern of services provided. Banks and customers are parties that act as communicants and communicators in transactions on financing products at Bank Muamalat Gorontalo. All operational activities of Bank Muamalat are carried out based on provisions based on Islamic law and the MUI Fatwa.